2021
DOI: 10.5897/jpbcs2021.0955
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting combining ability in a diallel cross between native and elite cucumber (Cucumis sativus L.) varieties

Abstract: F 1 progenies derived from a set of diallel crosses involving native and 5 elite cucumber varieties were evaluated in a randomized complete block design (RCBD) with three replications to study combining ability for some important agronomic traits. The analysis of variance revealed that the mean squares due to genotypes were significant for the traits studied, indicating wide diversity among the parents. Mean squares for general combining ability (GCA) and specific combining ability (SCA) were significant, impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…The average degree of heritability in the broad sense of the reverse effect was greater than the reciprocal effect, and the low degree of heritability in the narrow sense indicated that the additional action was less than the dominant action in the inheritance of these traits, and also indicated that the genetic effect was higher than the environmental effect of the traits, and for this reason it is possible to follow the hybridization method to improve most of the genetic traits of cucumbers grown in greenhouses by. These results have been agreed by [20], [21], [22] in cucumber and [23] in eggplant…”
Section: Greenhouse Yield (Ton Greenhousesupporting
confidence: 78%
“…The average degree of heritability in the broad sense of the reverse effect was greater than the reciprocal effect, and the low degree of heritability in the narrow sense indicated that the additional action was less than the dominant action in the inheritance of these traits, and also indicated that the genetic effect was higher than the environmental effect of the traits, and for this reason it is possible to follow the hybridization method to improve most of the genetic traits of cucumbers grown in greenhouses by. These results have been agreed by [20], [21], [22] in cucumber and [23] in eggplant…”
Section: Greenhouse Yield (Ton Greenhousesupporting
confidence: 78%
“…The high heterotic effect over standard parent was reported by Nimitha et (2018) for fruit yield per plant and number of fruits per plant in cucumber that can be used in commercial cultivation. Manggoel et al, (2021) reported the signi cant diversity between the cucumber genotypes studied. The ndings from this study showed the priority of dominant gene effects over additive gene effects for the genetic control of vine length and number of leaves per plant (Manggoel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Manggoel et al, (2021) reported the signi cant diversity between the cucumber genotypes studied. The ndings from this study showed the priority of dominant gene effects over additive gene effects for the genetic control of vine length and number of leaves per plant (Manggoel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%